Study on the Influence of Pregnancy-Induced Hypertension on Neonatal Birth Weight. (August 2018) - Lei, Fangliang; Liu, Danmeng; Shen, Yuan; Zhang, Lili; Li, Shanshan; Liu, Xin; Shi, Guoshuai; Li, Jiamei; Zhao, Yaling; Kang, Yijun; Dang, Shaonong; Yan, Hong
To explore the effect of pregnancy-induced hypertension (PIH) on neonatal birth weight and provide the necessary reference value for the maternal and children health service. A cross-sectional study was carried out in Shaanxi Province of China in 2013. And a total of 28 045 singleton live infants and their mothers were recruited using a stratified, multistage, probability-proportional-to-size sampling method. Among the 28 045 women of childbearing age surveyed, multiple linear regression and quantile regression analysis all showed that the birth weight of newborns whose mothers had suffered from PIH during pregnancy was significantly lower than those whose mothers had not suffered from PIH during pregnancy from very low to higher birth weight percentiles (q=0–0.85), an average decrease of 137.45 g (β=−137.45, t=−5.77 and p<0.001). When birth weight was at q=0.90–1.00 percentiles, there was no birth weight difference between two groups. The present cross-sectional study indicated that PIH had an effect of on neonatal birth weight. When pregnant women with PIH are identified then the healthcare professional initiates a closer supervision of their pregnancy in order to ameliorate the status of BP and provide a good intrauterine environment for the fetus. In addition, the gynecologists should admonish the pregnant women that their health is related to the health of their fetus, then gravidas may be more engaged to alert their physician and accept early or preventative interventions. And the healthcare professional should ask and be alert to the issues of hypertension during pregnancy.